2018
DOI: 10.1111/ivb.12210
|View full text |Cite
|
Sign up to set email alerts
|

Predatory behavior of giant Antarctic sea spiders (Colossendeis) in nearshore environments

Abstract: Pycnogonids in the genus Colossendeis are found in the deep sea and Southern Ocean. Although the genus contains the largest and most conspicuous species of sea spiders, little is known about their ecology or behavior. We documented two species feeding on a variety of benthic and pelagic invertebrates during three diving field seasons at McMurdo Station, Antarctica. Individuals of one species, Colossendeis megalonyx, fed on a variety of pelagic organisms, particularly the pteropod Clione antarctica. We used vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Indeed, in greater than 200 h of casual observation in the laboratory and field, we most often saw C. megalonyx walking across the substrate, while other species were more stationary. Likewise, C. megalonyx is capable of rapid and active capture of pelagic prey [35], and maximum escape speeds of C. megalonyx were almost twice as fast as those of A. glacialis (0.023 cm s 21 versus 0.013 cm s 21 ) [57]. Greater cuticle porosity may be one mechanism that allows C. megalonyx to evolve both large size and maintain high levels of activity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, in greater than 200 h of casual observation in the laboratory and field, we most often saw C. megalonyx walking across the substrate, while other species were more stationary. Likewise, C. megalonyx is capable of rapid and active capture of pelagic prey [35], and maximum escape speeds of C. megalonyx were almost twice as fast as those of A. glacialis (0.023 cm s 21 versus 0.013 cm s 21 ) [57]. Greater cuticle porosity may be one mechanism that allows C. megalonyx to evolve both large size and maintain high levels of activity.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that larger C. megalonyx may have a greater capacity for maintaining aerobic activity than small ones, which is consistent with the overall increase we found in righting performance with body size, although other factors might have affected this as well. Ecologically, larger body size may confer a fitness benefit on C. megalonyx because larger, more mobile animals have increased probabilities of encountering and capturing food [35]. The disproportionate increase in porosity with size may also reflect an ontogenetic shift in ecological feeding modes from comparatively stationary, parasitic juveniles to more mobile and actively predatory adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know little about predation on sea spiders in temperate regions (Burris, 2011), but both species in this study were found in high-current areas: A. chelata was collected from the shallow subtidal in Friday Harbor, where currents average 74.0 ± 15.2 cm s 21 (mean ± SD, based on 2018 daily maximum, NOAA Tides and Currents, https:// tidesandcurrents.noaa.gov/); and A. gracilipes was collected intertidally from a wave-swept site on the outer coast of the Pacific Northwest, a region where intertidal organisms experience very high water velocities and accelerations (Denny et al, 1985). The large-bodied sea spiders in the Antarctic experience low flow (3.6 cm s 21 over 10 months in McMurdo Sound; B. W. Tobalske et al, unpublished data, reported in Moran et al, 2018) and likely also experience low predation due to the lack of durophagous (crushing) predators in the Southern Ocean (Aronson et al, 2009;Moran and Woods, 2012). These and other factors may be more important than oxygen supply in setting the upper limits of body size of nonpolar pycnogonids.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in shallow and deep Antarctic and sub-Antarctic benthic habitats as well as around South America, South Africa, and Madagascar (Munilla and Soler-Membrives 2009). The feeding spectrum seems to be broad and even pelagic invertebrates are frequently consumed (Moran et al 2018). However, due to the fact that many cryptic species are known in that group, investigations of food preference have to be specified for each lineage before the abovementioned observations can be generalized (Dietz et al 2018).…”
Section: Introductionmentioning
confidence: 99%